The Responses of Carotenoids in Anabaena cylindrica to Single and Combined Metals of Nickel, Aluminum and Lithium - Tan, Yeong Hwang (AENSI Publications, 2015)
In the real polluted environment, the metals usually do not present in single pure form, but occur in mixture. Cyanobacteria are the most commonly available aquatic organisms in these environment, thus, there is a need to study the responses of carotenoids, a kind of antioxidant in cyanobacteria towards combined heavy and light metals. In this paper, Anabaena cylindrica was immobilized using agarose and exposed to the different concentration of single and combined Ni, Al and Li for 2 hours. The responses of carotenoids were determined using spectrophotometer at λ = 450 nm. The result showed that immobilized A. cylindrica responded differently to the exposure of single and combined metals. The cells were sensitive to single and combined Ni, Al and Li within the detection range of 0.001 mg/L to 10.000 mg/L. The value of R2 indicated the immobilized A. cylindrica responded in correlation to the concentration of the metals. Thus, A. cylindrica has the potential to be used as bioindicator for detection of single and combined metals.